Liver regeneration and carcinogenesis : molecular and cellular mechanisms - Jirtle, Randy L. (Academic Press, 1995)
Because of its marked capacity to regenerate and the ability of chemical carcinogens and viruses to ready transform hepatocytes, the liver has been used extensively as a model for investigating the molecular mechanisms of cellular proliferation and carcinogenesis. Recently, striking advances have occured in the understanding of hepatocyte growth regulation and the manner in which chemical agents and viruses alter these normal growth regulatory pathways in liver carcinogenesis. This explosion of information has occured in a multitude of researh disciplines. This book brings together current findings in a coherent manner, from a molecular point of view. Three sections cover in detail the areas of liver regeneration, liver carcinogenesis, and liver tumor therapy. The contributors are pioneers and leaders in this field. * Logical organization of material in three detailed and comprehensive sections: liver regeneration, liver carcinogenesis, and liver tumor treatment * Contributors are pioneers and leaders in the field * There are currently no books on this subject on the market * Research focus is at the molecular level.